Weibull verification of reduced pressure test as a tool for assessing Al melt quality. (4th March 2017) - Bartar Esfahani, Hosein; Raiszadeh, Ramin; Doostmohammadi, Hamid
Abstract: The credibility of reduced pressure test (RPT) as a substitute for Weibull analysis for benchmarking bifilm defects in Al alloys was confirmed by comparing the RPT parameters (2D and 3D porosity, and Bifilm Index) with the Weibull moduli for UTS values for pure Al and Al-0.05Sr alloys. The porosity of RPT samples was found to have an exponential decay relationship with Weibull modulus. A reasonable trend for Bifilm Index could not be found. 3D porosity of RPT samples was found to be more favourable than 2D porosity or Bifilm Index. Some evidence was also found of connections occurring between the sides of bifilm defects at the surfaces of the fractured tensile test bars of Al-0.05Sr alloy which had a relatively high UTS.